Translation of CRISPR Genome Surgery to the Bedside for Retinal Diseases - Xu, Christine L.; Cho, Galaxy Y.; Sengillo, Jesse D.; Park, Karen S.; Mahajan, Vinit B.; Tsang, Stephen H. (Frontiers in Cell and Developmental Biology, 2018)
In recent years, there has been accelerated growth of clustered regularly interspaced short palindromic repeats (CRISPR) genome surgery techniques. Genome surgery holds promise for diseases for which a cure currently does not exist. In the field of ophthalmology, CRISPR offers possibilities for treating inherited retinal dystrophies. The retina has little regenerative potential, which makes treatment particularly difficult. For such conditions, CRISPR genome surgery methods have shown great potential for therapeutic applications in animal models of retinal dystrophies. Much anticipation surrounds the potential for CRISPR as a therapeutic, as clinical trials of ophthalmic genome surgery are expected to begin as early as 2018. This mini-review summarizes preclinical CRISPR applications in the retina and current CRISPR clinical trials.